Post-exposure prophylaxis for human immunodeficiency virus: knowledge and experience of junior doctors - Chen, M (BMJ Group, 2001)
Objective: To assess the level of knowledge and experience of post-exposure prophylaxis (PEP) against human immunodeficiency virus (HIV) among junior doctors. Methods: A questionnaire was sent to all junior doctors working in two major teaching hospitals in London. Results: Most junior doctors had heard of PEP (93%) but fewer were aware that it reduced the rate of HIV transmission (76%). Only a minority of doctors (8%) could name the drugs recommended in recent national guidelines and a significant proportion (43%) could not name any. Almost one third (29%) did not know within what period PEP should be administered. This was despite the fact that the majority of respondents (76%) had experienced high risk exposure to potentially infective material at some stage in their careers and that a significant proportion (18%) had sought advice about PEP following potential exposures. Conclusions: This study demonstrates that the junior hospital doctors in our survey had inadequate knowledge of PEP against HIV despite being at risk of occupational exposure. Key Words: HIV; post-exposure prophylaxis; needlestick injuries